Living and immortal polymerization of seven and six membered lactones to high molecular weights with aluminum salen and salan catalysts. (January 2016) - MacDonald, Jarret P.; Sidera, Mireia; Fletcher, Stephen P.; Shaver, Michael P.
Graphical abstract: Highlights: Aluminium salen and salan complexes mediate the ROP of caprolactones. Rapid polymerization even at room temperature. High molecular weight PCL accessible under controlled and immortal conditions. Introduction of benzyloxy substituent for future post-polymerization modification. Abstract: The ring-opening polymerization (ROP) of seven membered aliphatic cyclic esters with aluminum salen (MeAl[salen]) and salan (MeAl[salan]) catalyst is reported. While the controlled polymerization of lactide and β-butyrolactone is known for these systems, the living polymerization of ɛ-caprolactone (ɛ-CL) was poorly controlled. We now report excellent levels of control upon optimization of reaction concentration, time and temperature. High molecular weight polycaprolactone (PCL), up to 175 kDa, was also prepared with exceptional dispersity control. Immortal polymerization was also studied, with up to 100 equivalents of chain transfer alcohol and 10, 000 monomer equivalents tolerated without any sacrifice to polymer control. 6-Methyl-ɛ-caprolactone (6-Me-ɛ-CL) and 2, 6-dimethyl-ɛ-caprolactone (2, 6-Me-ɛ-CL) were subjected to ROP conditions and low rates of polymerization were observed. Polymerization of 4-(4-benzyloxybutyl)-ɛ-caprolactone (4-BOB-ɛ-CL) was achieved with excellent control over dispersity and molecular weight, allowing introduction of functional groups into the polymer backbone. A block copolymer with 4-BOB-ɛ-CL and ɛ-CL was also prepared to produce a family of polymers with predictable composition.